2022
DOI: 10.1002/lsm.23599
|View full text |Cite
|
Sign up to set email alerts
|

Combination 1550 nm non‐ablative fractional resurfacing and laser hair removal for treatment of Becker's nevi in skin types III–VI

Abstract: Objectives Becker's nevus is a cosmetically bothersome benign hamartoma typically associated with basal layer hyperpigmentation and hypertrichosis. We herein present the largest case series characterizing treatment parameters and clinical outcomes of combined 1550 nm non‐ablative fractional resurfacing and laser hair removal (long‐pulsed neodymium‐doped yttrium aluminum garnet or alexandrite) in the treatment of Becker's nevus. This is also the largest case series of laser treatment of Becker's nevus in Fitzpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Balaraman et al 17 undertook a retrospective analysis of Becker's nevus removal through the combined use of 1550 nm nonablative fractional photothermolysis and laser hair removal, confirming the safety and utility of the modalities when used together. In a recent retrospective review, Kubicki et al 18 reported the safe and efficacious outcomes of combined 1550 nm nonablative fractional resurfacing and laser hair removal in 22 patients with Becker's Nevi. These favorable results of 1550 nm nonablative fractional laser, in addition to, the results observed in our current study should trigger a future work by combining 1550 and 1927 nm nonablative fractional laser wavelengths in managing Becker's Nevi and possibly attain better outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balaraman et al 17 undertook a retrospective analysis of Becker's nevus removal through the combined use of 1550 nm nonablative fractional photothermolysis and laser hair removal, confirming the safety and utility of the modalities when used together. In a recent retrospective review, Kubicki et al 18 reported the safe and efficacious outcomes of combined 1550 nm nonablative fractional resurfacing and laser hair removal in 22 patients with Becker's Nevi. These favorable results of 1550 nm nonablative fractional laser, in addition to, the results observed in our current study should trigger a future work by combining 1550 and 1927 nm nonablative fractional laser wavelengths in managing Becker's Nevi and possibly attain better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…16 Balaraman et al 17 undertook a retrospective analysis of Becker's nevus removal through the combined use of 1550 nm nonablative fractional photothermolysis and laser hair removal, confirming the safety and utility of the modalities when used together. In a recent retrospective review, Kubicki et al 18 study of the Saudi population attempted to resolve Becker's nevus using laser treatment with the Er:YAG laser, and unfavorable outcomes were reported. Lee et al 20 performed laser treatment using a 1927-nm fractional laser in cupping-related postinflammatory hyperpigmentation in a 26-year-old woman for 6 months, and positive benefits were confirmed.…”
Section: Discussionmentioning
confidence: 99%